Effects of Vacuum Bagging Techniques on Mechanical Properties of CarbonEpoxy Laminates - Norafizal, Arif Isyraf (IRC, 2020)

(untitled)
Conventionally, composite laminates were manufactured by applying vacuum bagging setup in an autoclave machine. However, the process needs a long production time and requires high-cost equipment. Alternatively, vacuum-bagging-only techniques are introduced as it does not require an autoclave vessel for the manufacturing procedure. However, this alternative suffers from manufacturing-induced defects such as void formation which will affect the mechanical properties of the produced laminates. This study investigates the effects of vacuum-bagging techniques and curing profiles on the void formation of carbon-epoxy laminates with complex shapes.